Effect of diethyl ether and ethanol on performance, combustion, and emission of single-cylinder compression ignition engine. Issue 1 (2nd January 2017) - Paul, Abhishek; Panua, Raj Sekhar; Debroy, Durbadal; Bose, Probir Kumar
Abstract : The effect of diesel, ethanol, and diethyl ether (DEE) blends on performance, combustion, and emission of a 3.6 kW single-cylinder compression ignition engine is investigated in this paper. The experiments were conducted using different percentages of ethanol and DEE in diesel. The fuel samples selected for experimentation included neat diesel fuel, 5% DEE (D95DEE5), 10% DEE (D90DEE10), 5% DEE with 5% ethanol (D90DEE5E5), 5% DEE with 10% ethanol (D85DEE5E10), 10% DEE with 5% ethanol (D85DEE10E5), and 10% DEE with 10% ethanol (D80DEE10E10). It was found that 5% DEE can improve the brake thermal efficiency ( η bth ), but the same decreased with 10% DEE in the blend. However, ethanol addition to both the blends produced an appreciable increase in η bth of the engine. The diesel–DEE–ethanol blends were also more efficient in reducing emissions of carbon monoxide (CO), oxides of nitrogen (NO x ), hydrocarbon (HC), and particulate matter (PM). Among all the blends tested in this study, it was found that the D80DEE10E10 blend can produce optimum performance-emission characteristics with improved thermal efficiency and reduced emission of NO x, CO, HC, and PM.